KEGIATAN ROHANI ISLAMI MELALUI PEMBELAJARAN PAI UNTUK MENINGKATKAN AKHLAK SISWA DI SMAN 1 RANGKASBITUNG KABUPATEN LEBAK - Midya'udin, Ahmad (Fakultas Agama Islam, Universitas Mathla'ul Anwar, 2023)
The aim of the research is to explore Islamic spiritual activities in schools and to improve students' morals as a whole and gain a deeper understanding of the teachings of the Islamic religion and be able to implement them in everyday life. The research uses field research, namely data collection is carried out in the field, such as in the community environment, social institutions or organizations, and government institutions. The data collection technique is through observation, interviews and documentation. The results and discussions obtained from spiritual formation show that there are several values that are expected from the implementation of express Islamic boarding schools, namely: First, the instillation of moral values, faith and devotion as well as good morals. Second, applying the discipline of togetherness and developing creativity, directed at student independence. Third, develop social solidarity and social solidarity. Apart from that, efforts are also made to establish a friendly relationship between the instructor and the students.